Constituents of "teabacco": A forensic analysis of cigarettes made from diverted nicotine replacement therapy lozenges in smoke‐free prisons. Issue 1 (14th August 2018) - Mitchell, Courtney; Puljević, Cheneal; Coomber, Ross; White, Alan; Cresswell, Sarah L.; Bowman, Jasper; Kinner, Stuart A.
Abstract: Following the implementation of prison smoke‐free policies, there have been reports of prisoners creating substitute cigarettes made from nicotine replacement therapy patches or lozenges infused with tea leaves ("teabacco"). No studies have analyzed the chemical constituents of teabacco made from nicotine lozenges, so as to document any potential related health hazards. Teabacco samples were made by a participant who reported creating teabacco while incarcerated in a smoke‐free prison in Queensland, Australia, and the process was video‐recorded for replication in a laboratory. A simple linear smoking system captured the teabacco smoke for analysis. Inductively coupled plasma optical emission spectroscopy (ICP–OES) was used to analyze elemental composition and gas chromatography coupled with a mass spectrometer (GC–MS) analyzed the captured smoke using the National Institute of Standards and Technology mass spectral library. Analyses determined that quantities of copper, aluminum, and lead concentrations, and levels of inhaled total particulate matter, were above recommended guidelines for safe ingestion. Analysis of teabacco smoke using GC–MS identified potentially toxic compounds catechol and nicotine. However, our findings show that smoking this form of teabacco is less harmful than smoking teabacco made from nicotine patches, or smoking traditional tobacco cigarettes. Considering the limited potential health harm of smoking teabacco made from lozenges, and that nicotine lozenges represent the only form of smoking cessation support for individuals entering smoke‐free prisons, we caution against the removal of nicotine lozenges from Queensland's prisons, at least until further research directly establishes health harms associated with this form of teabacco. Abstract : "Teabacco" cigarettes are substitute cigarettes made from a mixture of nicotine lozenges and tea leaves made by prisoners in response to smoke‐free policies. Teabacco made from nicotine lozenges contains some potentially harmful toxins but is less harmful to smoke than teabacco made from nicotine patches or traditional cigarettes.